1998
DOI: 10.1134/1.567874
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of localized electron pairs above the magnetic-field-driven superconductor-insulator transition in amorphous In-O films

Abstract: We have investigated the field-induced superconductivity-destroying quantum transition in amorphous indium oxide films at low temperatures down to 30 mK. It has been found that, on the high-field side of the transition, the magnetoresistance reaches a maximum and the phase can be insulating as well as metallic. With further increasing magnetic field the film resistance drops and approaches in the high-field limit the resistance value at transition point so that at high fields the metallic phase occurs for both… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
91
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 14 publications
12
91
1
Order By: Relevance
“…[7][8][9] Theoretical descriptions of this CPI phase often presume that disorder or magnetic field creates islands of Cooper pairs embedded in a non-superconducting background. [10][11][12][13] Although the description of the CPI as an inhomogeneous phase of matter is consistent with observations, the experimental support is limited. The most direct support provided so far is Scanning Tunneling Microscopy (STM) measurements which show evidence of spatial superconducting gap variations of ≲ 20% in superconducting films of InO x and TiN.…”
mentioning
confidence: 69%
“…[7][8][9] Theoretical descriptions of this CPI phase often presume that disorder or magnetic field creates islands of Cooper pairs embedded in a non-superconducting background. [10][11][12][13] Although the description of the CPI as an inhomogeneous phase of matter is consistent with observations, the experimental support is limited. The most direct support provided so far is Scanning Tunneling Microscopy (STM) measurements which show evidence of spatial superconducting gap variations of ≲ 20% in superconducting films of InO x and TiN.…”
mentioning
confidence: 69%
“…3 (with notable exceptions [21]). To fix problems with scaling like those in Fig 3a, Gantmakher suggested that the critical field corresponds to where the 2nd derivative of the resistance with respect to temperature is zero rather than the first derivative [30]. Until theory justifies this modification it seems more reasonable to assume that no critical field exists.…”
mentioning
confidence: 99%
“…At finite temperatures, a quantum phase transition is influenced by the thermal fluctuations, and according to the theory, (i) the film resistance R near the magnetic-field-induced SIT at low temperature T in the vicinity of the critical field B c is a function of one scaling variable δ = (B − B c )/T 1/νz , with the critical exponents ν and z being constants of order of unity, and (ii) at the transition point, the film resistance is of the order h/(2e) 2 ≈ 6.5 kΩ (the quantum resistance for Cooper pairs). Although much work has been done, and in many systems the scaling relations hold [3,4,5,6,7,8], the magnetic-field-induced SIT in disordered films remains a controversial subject, especially concerning the insulating phase and the bosonic conduction at B > B c . There is experimental evidence [7] that, despite the magnetoresistance being nonmonotonic, and in the magnetic fields above the critical one, the derivative of resistance dR/dT is negative, the phase can be insulating as well as metallic.…”
mentioning
confidence: 99%